Effects of Nearly Frontal and Highly Inclined Interplanetary Shocks on High‐Latitude Field‐Aligned Currents (FACs). Issue 12 (10th December 2019) - Shi, Yining; Oliveira, Denny M.; Knipp, Delores J.; Zesta, Eftyhia; Matsuo, Tomoko; Anderson, Brian
Abstract: We present high‐latitude field‐aligned current (FAC) response to nearly frontal shocks (NFSs) and highly inclined shocks (HISs) through a superposed epoch analysis. The FACs are derived from magnetic perturbation data provided by the Active Magnetosphere and Planetary Electrodynamics Response Experiment program. Forty‐nine events for each group are used for the superposed epoch analysis. The 25%, 50%, and 75% quantiles of the FAC and total current distributions are studied. We found that NFSs are statistically stronger shocks in terms of solar wind parameters such as solar wind speed and interplanetary magnetic field.For the 50% quantiles, both groups of shocks produce rapid increases in total currents after shock arrival, but NFSs result in sharper increase in FACs and more intense FACs compared to HISs. At the 50% and 75% quantiles, NFSs trigger stronger auroral‐zone current disturbance for the first hour after shock arrival than do HISs. Spatially, the difference in FAC response is most notable in (1) the dayside noon region, (2) the duskside Region 2 current system, and (3) the dawnside prenoon Region 1 current system. Our results are consistent with previous numerical simulations that showed more symmetric and stronger compression of the magnetosphere for high‐speed and nearly frontal shocks. We observationally confirm the role of shock impact angle in controlling the subsequent shock geoeffectiveness for fast shocks. We assert that determining the shock impact angle via an upstream solar wind model could provide useful insight in forecasting the geoeffectiveness of a shock prior to its arrival at the magnetopause. Key Points: Fast, nearly frontal shocks result in sharper increase in FACs and more intense FACs in the first hour after shock arrival Nearly frontal shocks are generally stronger interplanetary shocks compared to highly inclined shocks in terms of solar wind parameters Clearest spatial response difference between NFSs and HISs shows around noon, duskside R2 currents and pre‐noon R1 currents